Identification and Application of a Panel of Constitutive Promoters for Gene Overexpression in Staphylococcus aureus - Liu, Qiang; Li, Daiyu; Wang, Ning; Guo, Gang; Shi, Yun; Zou, Quanming; Zhang, Xiaokai (Frontiers in Microbiology, 2022)
Staphylococcus aureus is a leading pathogen that is currently the most common cause of infection in hospitalized patients. An in-depth genetic analysis of S. aureus virulence genes contributing to pathogenesis is needed to develop novel antimicrobial therapies. However, tools for genetic manipulation in S. aureus are limited, particularly those for gene expression. Here, 38 highly expressed genes were identified in S. aureus USA300_FPR3757 via RNA-seq. Promoter regions from 30 of these genes were successfully cloned, of which 20 promoters exhibited a wide range of activity. By utilizing these active promoters, 20 S. aureus-E. coli shuttle vectors were constructed and evaluated by expressing an egfp reporter gene. Expression of egfp gene under the control of different promoters was confirmed and quantified by Western-blot and qPCR, which suggested that the activity of these promoters varied from 18% to 650% of the activity of PsarA, a widely used promoter for gene expression currently. In addition, our constructed vectors were verified to be of high compatibility for gene expression in different S. aureus strains. Furthermore, these vectors were evaluated and used in overexpressing two endogenous proteins in S. aureus, namely, catalase and the transcriptional repressor of purine biosynthesis (PurR). Meanwhile, the physiological functions and phenotypes of overexpressed PurR and catalase in S. aureus were validated. Altogether, this evidence indicates that our constructed vectors provide a wide range of promoter activity on gene expression in S. aureus. This set of vectors carrying different constitutive promoters developed here will provide a powerful tool for the direct analysis of target gene function in staphylococcal cells.